Association of estrogen receptor single nucleotide polymorphisms and perinatal depression - Richelle Duque Björvang; Lulu Francis Gumbo; Anders Årdahl; Susanne Lager; Erika Comasco; Emma Fransson; Alkistis Skalkidou (PLoS ONE, 2025)
Depression during pregnancy and in the postpartum period have been receiving increasing attention considering the possible complications for the mother and baby if left untreated. Genetic variations in the estrogen receptor genes (ESR) have been implicated in susceptibility to depression. However, only few studies investigated them in perinatal depression (PND) and none on its different trajectories (i.e., patterns of time of onset and persistency of depression). Here, we explored the association of single nucleotide polymorphisms (SNPs) of the ESR1 and ESR2 genes with PND among 2,973 women in Sweden. PND was defined using the Edinburgh Postnatal Depression Scale, the Depression Self-Rating Scale, use of selective serotonin reuptake inhibitor, and/or medical records. PND trajectories were identified as follows: controls (no depression at any point in the perinatal period), antepartum (depression during pregnancy and resolved postpartum), postpartum-onset (no depression during pregnancy with onset after delivery), and persistent (depression throughout the perinatal period). Multivariable logistic regression was performed. Out of 56 SNPs analyzed, one SNP in the ESR1 gene (rs2982712) was nominally significantly associated with PND (OR 0.83, 95% CI 0.71–0.98, p = 0.03) as well as with persistent depression (OR 0.77, 95% CI 0.61–0.98, p = 0.03) in the overdominant model (DD/dd vs. Dd). In addition, we also found two SNPs, namely rs1884051 (OR 0.74, 95% CI 0.56–0.98, p = 0.03) and rs2228480 (OR 0.77, 95% CI 0.60–0.99, p = 0.04) in the ESR1 gene, that were nominally significantly associated with persistent depression only. None of the ESR1 SNPs were associated with antepartum or postpartum-onset depression. None of the ESR2 SNPs, nor any haplotypes, were associated with PND or its trajectories. Our findings suggest a role of ESR1 in PND, especially its persistent trajectory.